Isu-Isu Pendidikan Islam Kontemporer: Tantangan Globalisasi dan Modernisasi - Ahmad Muyadi; Dwi Noviani (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This study aims to identify and analyze the challenges of Islamic education in the era of globalization and modernization. The discussion focuses on what is meant by globalization and modernization? What are the Issues of Islamic Education in the Era of Globalization and Modernization? And what are the challenges of Islamic education in the era of globalization and modernization. Data was obtained through literature study and then analyzed for its relevance to actual facts occurring today. There are three main challenges currently faced by Islamic education, namely advances in science and technology, democratization, and the cultural sector. In essence, Islamic education institutions must reform their curriculum so that they can prepare superior human resources and have competitiveness in facing global competition and Islamic education must continue to make improvements and innovate and work hard to improve existing weaknesses.